ASPECTS OF COMPARATIVE LAW IN THE MATTER OF JUVENILE PRE-DELINQUENCY AND DELINQUENCY WITH TRENDS TOWARDS SANCTIONS AND PREVENTION - MONICA POCORA; MIHAIL-SILVIU POCORA (Challenges of the Knowledge Society, 2013)
This study aims to be an interdisciplinary, criminal-criminological approach of the minority institution in terms of criminal liability, with an evolutionary dynamic of the pre-offense and post-offense assumptions. The operative criterion is the notion of juvenile pre-delinquency (pre-deviance or potential deviance), because it refers to all the acts violating the norm of moral behaviour, which in certain circumstances may lead a teenager to appear before the court, and in other circumstances not. The deviant conducts of minors do not necessarily have a criminal nature and not under all circumstances. If these different acts of them do not violate the criminal norms, representing only deviations from ethical rules of behaviour, they are not legally sanctioned, but only in moral forms. Thus, this approach is meant to be a criminological transition from the criminological plan to the criminal illegality.